Characterization of gut microbiome dysbiosis in calcium oxalate stone patients with comorbid metabolic syndrome - Batur, Maimaitiaili; Li, Xun; Liu, Bide; Wang, Shuheng; Dong, Qiang; Abudurexiti, Nueraili; Liu, Zewei (Frontiers in Microbiology, 2025)
ObjectiveMetabolic syndrome is an important risk factor for calcium oxalate stone, yet the underlying mechanism remain unclear. Gut microbiota is involved in human metabolic processes and is associated with both metabolic syndrome and calcium oxalate stone formation.MethodsIn this study, 100 subjects were divided into four groups: calcium oxalate stone with metabolic syndrome (Group A), metabolic syndrome only (Group B), calcium oxalate stone only (Group C), and healthy controls (Group D), with 25 cases in each group. Gut microbiota composition and function were analyzed using 16S rRNA gene sequencing. Microbiota diversity, species differences, and metabolic function changes were assessed by combining clinical parameters and metabolic pathway (KEGG) annotation.ResultsThe α diversity in Group A was significantly lower than in the other three groups (Shannon index, P < 0.05), and β diversity analysis revealed significant differences in bacterial community structure among all four groups (ANOSIM, P < 0.05). In Group A, short-chain fatty acid (SCFA)-producing probiotics (e.g., Faecalibacterium, Faecalibacillus, Prevotella) were reduced, while pro-inflammatory bacteria (e.g., Eggerthella and Anaerobacteriaceae) were enriched. RDA correlation analysis indicated that Faecalibacterium is negatively correlated with blood glucose levels, Faecalibacterium and Roseburia are positively correlated with urinary pH. KEGG analysis showed that the bisphenol degradation pathway was reduced (logFC = −1.45, P = 0.027) and the retinol metabolism pathway was enriched (logFC = 0.928, P = 0.006) in Group A compared to Group B.ConclusionPatients with calcium oxalate stone and metabolic syndrome exhibit a “double imbalance” in gut microbiota: on the one hand, the reduced diversity of the microbiota and the decrease of SCFAs-producing microbiota weakened the metabolic protective effect of the gut microbiota; on the other hand, the enrichment of pro-inflammatory and pathogenic bacteria exacerbated metabolic disorders and inflammatory reactions. The present study reveals that gut microbiota play a role in the mechanism of metabolic syndrome promoting calcium oxalate stone formation, and these findings provide a theoretical basis for the use of probiotics to prevent calcium oxalate stone.